2015
DOI: 10.1007/s00261-015-0478-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative CT predictors associated with 30-day adverse events in patients with appendiceal inflammatory masses who underwent immediate appendectomies

Abstract: High-grade obstruction was an independent pre-operative CT predictor associated with 30-day adverse events in patients who underwent immediate appendectomies for appendiceal inflammatory masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Previous studies have investigated variables affecting outcomes according to individual treatment approach [121314151617]. Our recent study reported that high-grade obstruction identified on preoperative CT is a predictor associated with 30-day adverse events in patients who underwent immediate appendectomy for appendiceal inflammatory mass [12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have investigated variables affecting outcomes according to individual treatment approach [121314151617]. Our recent study reported that high-grade obstruction identified on preoperative CT is a predictor associated with 30-day adverse events in patients who underwent immediate appendectomy for appendiceal inflammatory mass [12].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study reported that high-grade obstruction identified on preoperative CT is a predictor associated with 30-day adverse events in patients who underwent immediate appendectomy for appendiceal inflammatory mass [12]. However, that study did not explore the impact of high-grade obstruction on outcomes in patients with appendiceal inflammatory mass treated nonoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations